Therapeutic drug monitoring of corticosteroids/β2-agonists in the hair of patients with asthma: an open-label feasibility study - Salvator, Hélène; Lamy, Elodie; Roquencourt, Camille; Bardin, Emmanuelle; Devillier, Philippe; Grassin-Delyle, Stanislas (Frontiers in Pharmacology, 2024)
Background: Although adherence to inhaled medication is critically important for treatment efficiency, around half of patients taking these drugs are non-adherent or make critical errors when using their delivery device. Segmental hair analysis might be a valuable tool for therapeutic monitoring because hair concentrations reflect exposure from month to month. The objective of the present proof-of-concept study was to establish the feasibility of segmental hair analysis of inhaled budesonide and formoterol in asthma patients. Methods: We conducted a prospective, open-label, interventional study of adult patients being treated with budesonide/formoterol for controlled, moderate-to-severe asthma (CorticHair, NCT03691961). Asthma control, lung function, and medication adherence were recorded. Hair samples were taken 4 months after enrolment and cut into four 1 cm segments. Results: Samples were available from 21 patients (20 women; median age: 53; median budesonide dose: 600 μg/d). Budesonide and formoterol were detected in samples from 18 to 13 patients, respectively. The median hair concentrations were 6.25 pg/mg for budesonide and 0.9 pg/mg for formoterol. The intrapatient coefficient of variation between hair segments was 21% for budesonide and 40% for formoterol. Pearson’s coefficients for the correlations between the hair concentration and the self-reported drug dose and the prescribed drug dose were respectively 0.42 (p = 0.08) and 0.29 (p = 0.25) for budesonide and 0.24 (p = 0.44) and 0.17 (p = 0.57) for formoterol. Conclusion: Segmental hair analysis of inhaled medications was feasible, with low intrapatient variability. This innovative, non-invasive means of assessing monthly drug exposure might help physicians to personalize drug regimens for patients with difficult-to-treat asthma.